THE EFFECTIVENESS OF MATHEMATICS LEARNING WITH SCIENTIFIC APPROACH THROUGH THE COOPERATIVE MODEL OF TYPE NUMBERED HEADS TOGETHER IN TERMS OF STUDENT ACHIEVEMENT OF GRADE X SMA NEGERI 1 KALASAN - Hildegardis Mulu Hildegardis Mulu; Sahid Sahid (Universitas Negeri Yogyakarta, 2016)
The purposes of this research were to know the effectiveness of mathematics learning with scientificapproach through the cooperative model of type numbered heads together (NHT) in terms of student achievement,the effectiveness of mathematics learning with scientific approach in terms of student achievement, and to knowwhich one was more effective between mathematics learning with scientific approach through the cooperativemodel of type NHT and with scientific approach without NHT in terms of student achievement. This research usedquasi-experimental with pre-test and post-test control group design. Its population was all students of grade X SMANegeri 1 Kalasan. The samples were class X MIA 2 as experiment class which given scientific approach throughthe cooperative model of type NHT and class X MIA 1 as control class which given scientific approach. Theinstruments used in this research were learning instrument, i.e. lesson plan and student worksheet, pre-test and posttest as test instrument to measure student achievement, and observation sheets as non-test instrument. Thehypotheses testing used were one sample t-test and independent sample t-test. The results indicated thatmathematics learning with scientific approach through the cooperative model of type NHT was effective in termsof student achievement. Mathematics learning with scientific approach was also effective in terms of studentachievement. But, the post-test result means between the two classes were not significantly different. So, themathematics learning with scientific approach through the cooperative model of type NHT was not more effectivethan mathematics learning with scientific approach without NHT in terms of student achievement.